Analysis of Respondent Characteristics and Risk Factors Related to the Incidence of Opportunistic Infections in People With HIV/AIDS (ODHIV) in Gorontalo City - Fatrina M. Gani; Irwan; Ayu Rofia Nurfadillah (Universitas Muhammadiyah Palu, 2025)
The decline in immune system function due to HIV in individuals with AIDS is closely related to opportunistic infections (Ols) Ols in People Living with HIV/AIDS (PLWHA) are infections that occur due to impaired immune function This study aims to analyze respondent characterisues and risk factors associated with opportunistic infections in PLWHA in Gorontalo City This study employs a quantitative analytical method with a cross-sectional study design. The study was conducted at the KPA (AIDS Handling Commission) of Gorontalo Province over a one-day period. The sampling technique used was total sampling, with a total of 35 respondents The results indicated that of the 35 PLWIHA, 23 experienced Ols The characteristics of the respondents with the highest frequency were female (18) respondents. 51. 49%), aged 24 years (25 respondents, 71.4%), with higher education (22 respondents, 62.96 unmarried or divorced (27 respondents, 77 1%1, and living with HIV for 5 years (2) respondents, 60 01 Bivartate analysis revealed that education level, marital status, occupation CD4 count HIV stage, and adherence to ARV medication were sunificantly associated with the occurrence of Ols Multivariate analysis identified three dominant variables influencing Of occurrence occupation CD4 count and ARV adherence It is recommended that PL WHA adhere more strictly to ARV medication to strengthen the immune system.